2007
DOI: 10.1007/s00428-006-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

MYH, OGG1, MTH1, and APC alterations involved in the colorectal tumorigenesis of Korean patients with multiple adenomas

Abstract: This study was done to characterize base excision repair (BER) genes and adenomatous polyposis coli (APC) alterations in the tumorigenesis of multiple colorectal adenomas in Korean patients. In total, 217 adenomas (mean number = 10) and 117 cancers were available from 143 patients. The heterozygous genotype of OGG1 c.1-18G>T was closely associated with multiple adenoma families (P < 0.001), while MYH A359V mutation exhibited a tendency (P = 0.053). MYH R170G mutation was exclusively identified in one patient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
2
10
1
Order By: Relevance
“…The inactivation or induction of the corresponding TF can modulate the expression of the hOGG1 gene, thus influencing the activity of the protein (31,32). Previous studies revealed that certain types of functional variants in the 5'-UTR of the hOGG1 gene are capable of increasing the risks of diseases, including cancer (9,11,33,34). The present finding suggests that there was no significant correlation between the variants in hOGG1 and the PCOS risk.…”
Section: A B Discussioncontrasting
confidence: 37%
“…The inactivation or induction of the corresponding TF can modulate the expression of the hOGG1 gene, thus influencing the activity of the protein (31,32). Previous studies revealed that certain types of functional variants in the 5'-UTR of the hOGG1 gene are capable of increasing the risks of diseases, including cancer (9,11,33,34). The present finding suggests that there was no significant correlation between the variants in hOGG1 and the PCOS risk.…”
Section: A B Discussioncontrasting
confidence: 37%
“…The functional variation of the hOGG1 gene has been reported to contribute to a high risk for cancer. In the 5Ј-UTR of the hOGG1 gene, Kim et al (2007) reported that c.¡18G>T may play a role in colorectal cancer in a Korean population, and Ishida et al (1999) indicated that c.¡23A>G was associated with lung cancer in a small Japanese population. The hOGG1 gene p.Ser326Cys is a well-known variation.…”
Section: Introductionmentioning
confidence: 98%
“…However, majority of works on the relationship between variations of the hOGG1 gene and the risk of breast cancer have been focused on c.977C[G in exon7 [8]. Kim and Ishida [9,10] showed that c.-18G[T and c.-23A[G variations in hOGG1 gene could be functional polymorphisms, and play a role in the pathogenesis of multiple adenomas, colorectal cancer, and lung cancer, but inconsistent results have been reported on these variations [11,12]. No study has reported on the relationship between the risk of breast cancer and the polymorphisms in 5-untranslated region (5 0 -UTR) of the hOGG1 gene.…”
Section: Introductionmentioning
confidence: 99%